The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1038/sc.1988.40
|View full text |Cite
|
Sign up to set email alerts
|

Non-traumatic ischaemic myelopathy: a review of 25 cases

Abstract: SummaryThe causes of ischaemic myelopathy are described in 25 patients. Nine developed following surgical manipulation or traumatic laceration of the aorta, 1 following intercostal artery ligation, 3 following aortic aneurysm dissection, 2 following myo cardial infarction and/or cardiac arrest, 7 in the absence of any specifically iden tifiable predisposing factors, and 3 in association with decompression sickness. The degree of clinical recovery was greater among those with incomplete spastic (as opposed to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 31 publications
1
21
0
2
Order By: Relevance
“…6,7,[15][16][17][23][24][25]34,36 Our results confirm select neuropathological studies reporting the predominance of ischemic changes in the lumbosacral cord after a global ischemic episode. 15,17,24,25,34 Neuronal necrosis restricted to the lumbosacral level of the spinal cord was initially reported by Gilles and Nag 24 in 6 neonates suffering transient cardiopulmonary arrest. These findings were later confirmed in a larger series of premature infants with clinically documented hypotensive episodes 34 and 2 adult patients after cardiac arrest.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…6,7,[15][16][17][23][24][25]34,36 Our results confirm select neuropathological studies reporting the predominance of ischemic changes in the lumbosacral cord after a global ischemic episode. 15,17,24,25,34 Neuronal necrosis restricted to the lumbosacral level of the spinal cord was initially reported by Gilles and Nag 24 in 6 neonates suffering transient cardiopulmonary arrest. These findings were later confirmed in a larger series of premature infants with clinically documented hypotensive episodes 34 and 2 adult patients after cardiac arrest.…”
Section: Discussionsupporting
confidence: 81%
“…6,9,11,12 This pattern of vascularization of the spinal cord has been equated with increased sensitivity of this area to ischemic injury. There have been, however, individual case reports [13][14][15][16][17][18][19][20][21][22] and clinical 23 and clinicopathological studies 20,24,25 suggesting that global ischemia may affect the low thoracic and lumbosacral cord to a greater extent than the other levels of the spinal cord. We performed a retrospective review of neuropathological changes in the brains and spinal cords of survivors of cardiac arrests or severe hypotensive episodes to reevaluate the frequency and distribution of neuronal injury in the spinal cord associated with ischemic encephalopathy in adults.…”
mentioning
confidence: 99%
“…There are two thin posterior spinal arteries with a lower number of feeders. Kim et al 9 suggested that in case of impairment of perfusion (hypovolemia or cross-clamping and according to the site of cross-clamping), preferential damage involved the grey matter and was associated with a¯accid, lower motoneurone type of weakness. They also suggested that localised damage, such as is seen following a lesion of a major radicular artery, may lead to localised spinal cord infarction in its territory of supply.…”
Section: Discussionmentioning
confidence: 99%
“…Of these two had a preoperative paraplegia and one was neurologically unimpaired. Six had dissecting aortic aneurysms (3,7,8,9,11,12). All but one were neurologically unimpaired before the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Uma revisão da literatura permitiu-nos encontrar algumas referências sobre paraplegia, conseqüente à DAA, a maioria sob forma de relato de caso, sendo que nenhum autor reuniu mais do que três pacientes em suas casuísticas [11][12][13][14][15][16][17][18] . A paraplegia é atribuída a isquemia ou infarto da medula espinhal devido a interrupção do fluxo sangüíneo para as artérias espinhais anteriores e posteriores.…”
Section: Discussionunclassified